Optimizing manure management for enhancing millet yields and resources use efficiency under rehabilitated plinthosols in the Sahel - Ibrahim, A.; Fatondji, D. (Elsevier, 2020)
Availability of organic amendment for improving crop yields under rehabilitated degraded soils is a challenge in the Sahelian regions. There is, therefore, a need to develop an innovative manure management strategy for optimizing the use of available manure to increase crop yields in these regions. A 2-year field and litterbag experiments were conducted to determine the optimal manure application option for enhancing millet yield and resources use efficiency under rehabilitated degraded soil in Niger. Two rates of cattle manure (200 g and 300 g per zaï hole), and three modes of manure application (i) all before planting (M1), (ii) half before planting and half at planting (M2) and (iii) half at planting and half 15 days after planting (M3) were used. The highest manure mass loss (83%) occurred under M1 application mode followed by manure applied under M2. At the tillering stage, the quantity of N and K released from decomposing manure were markedly higher than nutrients absorbed by millet indicating a poor nutrient synchrony due to a rapid release of nutrient at the early stage of millet development. At the maturity stage, N, P and K absorbed by millet markedly exceeded nutrients released from manure irrespective of manure application period. Application of manure under M2 increased average millet grain yield by 50% and 14% compared to manure application under M1 and M3 modes, respectively. Increase in grain yield in response to manure application modes and rates was accompanied by significant increases in nutrient and rainwater use efficiencies in both years. These results indicate that split application of manure (half before planting and half at planting) enhances nutrient and rainwater utilization efficiencies for increased yields under rehabilitated degraded soil in the Sahel.